Two phase 3, double-blind, placebo-controlled studies of the efficacy and safety of Astodrimer 1% Gel for the treatment of bacterial vaginosis. (February 2020) - Chavoustie, Steven E.; Carter, Belvia A.; Waldbaum, Arthur S.; Donders, Gilbert G.G.; Peters, Klaus H.; Schwebke, Jane R.; Paull, Jeremy R.A.; Price, Clare F.; Castellarnau, Alex; McCloud, Philip; Kinghorn, George R.
Abstract: Objective: Astodrimer is a dendrimer formulated in a vaginal gel to treat bacterial vaginosis (BV) and prevent recurrence. The objective of these studies was to confirm the efficacy and safety of Astodrimer 1 % Gel for treatment of BV. Study Design: Women with bacterial vaginosis were randomized 1:1 to Astodrimer 1 % Gel (Study 1 conducted in the United States, N = 127; Study 2 conducted in the United States, Germany and Belgium, N = 128) or placebo gel (Study 1, N = 123; Study 2, N = 123) at a dose of 5 g vaginally once daily for 7 days. The primary endpoint was clinical cure, defined as i) absence of bacterial vaginosis vaginal discharge; ii) <20 % clue cells; and iii) negative whiff test at day 9–12. Secondary efficacy analyses included clinical cure at day 21–30. Other endpoints at days 9–12 and 21–30 included Nugent cure (Nugent score ≤3), absence of symptoms, and adverse events. The primary analysis in the modified intent-to-treat population used the Cochran Mantel Haenszel test stratified by analysis center with a two-sided significance level of α = .05. Results: Astodrimer 1 % Gel was superior to placebo for the primary and selected secondary efficacy measures. Clinical cure rates at day 9–12 were 50.4 % (59/117) vs 16.5 % (19/115, P < .001) (Study 1) and 56.7 % (68/120) vs 21.4 % (25/117, P < .001) (Study 2) for astodrimer vs placebo. At day 21–30, clinical cure results showed a similar trend but the difference to placebo was not statistically significant. Nugent cure rates at day 9–12 were 12.8 % (15/117) vs 2.6 % (3/115, P = .004) (Study 1) and 13.3 % (16/120) vs 5.1 % (6/117, P = .030) (Study 2) for astodrimer vs placebo. A greater proportion of women receiving astodrimer reported absence of vaginal discharge and absence of vaginal odor at day 9–12 and day 21–30 compared with placebo. Adverse events were generally mild and self-limiting. For the combined studies, adverse events potentially related to treatment occurred in 14.7 % (37/252) of astodrimer patients vs 9.4 % (23/244) for placebo, including vulvovaginal candidiasis reported for 2.4 % (6/252) of astodrimer patients. Conclusion: These results support a role for Astodrimer 1 % Gel as an effective, safe and well-tolerated treatment for women with bacterial vaginosis.